2013
DOI: 10.15835/nbha4129298
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Objectives and Selection Criteria for Milk Thistle [<i>Silybum marianum</i> (L.) Gaertn.] Improvement

Abstract: Milk thistle [Silybum marianum (L.) Gaertn.] is an important medicinal-industrial plant. The medicinal compounds of milk thistle are derived from its seeds. The plant is commercially cultivated for the production of silymarin. Cultivation offers the opportunity to optimise achene yield and silymarin content. Furthermore, efforts should be made to develop new cultivars. The main objective of milk thistle breeding is to develop high yielding cultivars with elevated silymarin content. There are few developed cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Similarly, Martin et al () also reported significant differences in silymarin content between years. The observed differences in silymarin concentration for the same populations during the research period were likely to have been due mainly to environmental conditions; in support of this, several authors have reported that silymarin content was affected by climatic conditions (Alemardan et al, ; Andrzejewska et al, ; Carrier, Crowe, Sokhansanj, Wahab, & Barl, ).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Similarly, Martin et al () also reported significant differences in silymarin content between years. The observed differences in silymarin concentration for the same populations during the research period were likely to have been due mainly to environmental conditions; in support of this, several authors have reported that silymarin content was affected by climatic conditions (Alemardan et al, ; Andrzejewska et al, ; Carrier, Crowe, Sokhansanj, Wahab, & Barl, ).…”
Section: Discussionmentioning
confidence: 64%
“…Milk thistle is mainly cultivated for silymarin production, but can be also be grown as an oilseed crop (Alemardan et al, ). In the present study, the oil content ranged between 24.65 and 31.10%, while the CV across all populations was only 5.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increasing interest in S. marianum as a multipurpose crop and its economic importance as an officinal species, only ten improved genotype/cultivars exist [Alemardan et al 2013]. The species is still marked by traits that are typical of non-domesticated plants: fruit scattering at maturity, asynchronous flowering, spiny leaves, variable yield stability and quality [Martinelli et al 2016].…”
Section: Introductionmentioning
confidence: 99%
“…As regard as both the plant morphology and the valuable fruit constituents, a wide phenotypic variability between accessions of different origins was observed but improved cultivars for these traits have not been released, yet [Ram et al 2005, Martinelli et al 2016. Hence, further genetic improvement is mandatory for the complete exploitation of milk thistle as a crop species [Alemardan et al 2013.…”
Section: Introductionmentioning
confidence: 99%